2019
DOI: 10.1101/679894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elizabethkingia anophelisresponse to iron stress: physiologic, genomic, and transcriptomic analyses

Abstract: 28Elizabethkingia anophelis bacteria encounter fluxes of iron in the midgut of mosquitoes, 29where they live as symbionts. They also establish bacteremia with severe clinical 30 manifestations in humans, and live in water service lines in hospitals. In this study, we 31 investigated the global gene expression responses of E. anophelis to iron fluxes in the midgut 32 of female Anopheles stephensi mosquitoes fed sucrose or blood, and in iron-poor or iron-rich 33 culture conditions. Of 3,686 transcripts revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
1
0
0
Order By: Relevance
“…Blood meal intake by the mosquitoes resulted in the proliferation of taxa such as Elizabethkingia [63][64][65] , Comamonadaceae 66 , Streptococcus 66 , Ralstonia 67 and Chryseobacterium. Our study corroborates the findings of 68,69 which demonstrated that E. anophelis is significantly increased after a blood meal uptake, furthermore, E. anophelis facilitates red blood cells lysis with several hemolysins potentially contributing to blood meal digestion in mosquitoes 30,70 . Understanding the role of these taxa in the vectorial capacity and transmission efficiency of Ae.…”
Section: Discussionsupporting
confidence: 91%
“…Blood meal intake by the mosquitoes resulted in the proliferation of taxa such as Elizabethkingia [63][64][65] , Comamonadaceae 66 , Streptococcus 66 , Ralstonia 67 and Chryseobacterium. Our study corroborates the findings of 68,69 which demonstrated that E. anophelis is significantly increased after a blood meal uptake, furthermore, E. anophelis facilitates red blood cells lysis with several hemolysins potentially contributing to blood meal digestion in mosquitoes 30,70 . Understanding the role of these taxa in the vectorial capacity and transmission efficiency of Ae.…”
Section: Discussionsupporting
confidence: 91%